Empiric Antibiotic Therapy of Nosocomial Bacterial Infections. (July 2016) - Reddy, Pramod
Abstract : Broad-spectrum antibiotics are commonly used by physicians to treat various infections. The source of infection and causative organisms are not always apparent during the initial evaluation of the patient, and antibiotics are often given empirically to patients with suspected sepsis. Fear of attempting cephalosporins and carbapenems in penicillin-allergic septic patients may result in significant decrease in the spectrum of antimicrobial coverage. Empiric antibiotic therapy should sufficiently cover all the suspected pathogens, guided by the bacteriologic susceptibilities of the medical center. It is important to understand the major pharmacokinetic properties of antibacterial agents for proper use and to minimize the development of resistance. In several septic patients, negative cultures do not exclude active infection and positive cultures may not represent the actual infection. This article will review the important differences in the spectrum of commonly used antibiotics for nosocomial bacterial infections with a particular emphasis on culture-negative sepsis and colonization.